The Effect Ricker Wavelet of Duty Cycle Adjustment on GPR Detection Result - Aditya Rifky Ramadhan; Erfansyah Ali; A.A. Pramudita (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2021)
Ground Penetrating Radar (GPR) employs an ultra-wideband (UWB) signal for detecting objects under the ground surface. In a certain GPR application, a proper UWB signal is needed to obtain a good detection result. Ricker wavelet is one type of UWB signal that can be used in GPR operation. The effect of adjusting the Ricker wavelet duty cycle on the B-scan result was investigated and the result is discussed in this paper. Laboratory experiments were performed by modelling the GPR system using Vector Network Analyzer (VNA). The result shows that selecting a Ricker wavelet’s duty cycle is successful to show the target clearly.